1998
DOI: 10.1046/j.1365-3083.1998.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

A Glycosylated Bence Jones Protein and its Autologous Amyloid Light Chain Containing Potentially Amyloidogenic Residues

Abstract: Amyloidosis is characterized by deposition of protein fibrils in various tissues. The wide variety of sequences of both amyloidogenic and non‐amyloidogenic immunoglobulin light chains makes them a unique tool for addressing the importance of primary structure in the formation of insoluble fibrils. In this study, we have determined the primary structure of the κ I immunoglobulin light chain from both the urinary Bence Jones protein and the deposited amyloid fibrils of a patient (MH) with primary amyloidosis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In positions 6 and 7, both Leu/Val and Gly/Arg, respectively, were seen which in part confirmed the data of tryptic peptides T-1 (pos. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and T-1a (pos. [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In positions 6 and 7, both Leu/Val and Gly/Arg, respectively, were seen which in part confirmed the data of tryptic peptides T-1 (pos. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and T-1a (pos. [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The purity of the sample was also checked by reverse-phase high performance liquid chromatography (RP-HPLC) as described 16 . Edman degradation was performed before and after treatment of the sample with pyroglutamylaminopeptidase (Boehringer-Manheim and Takara Shuzo Co., Ltd. Japan) according to Mozdzanowski et al 17 .…”
Section: Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2-DE and other high resolution electrophoretic methods are also being used increasingly to detect and characterise the carbohydrate constituents of glycoproteins by the use of lectin probes following immunoblotting. This may be of particular interest in studies of nephrotoxicity as BJ proteins are glycosylated [91, 149±152] and differential glycosylation is of pathophysiological significance [153] in dictating tissue uptake of free LC [154] and fibrillogenesis [155].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 amyloidogenic glycosylated LCs in Stevens study, most of them (13/18) also had other PTMs (including S-cysteinylation, fragmentation, dimerization and S-sulfonation), so a definitive role for glycosylation is difficult to delineate. Other studies also implicated glycosylation as an important characteristic among amyloidogenic proteins (Dwulet et al, 1986;Engvig et al, 1998;Foss et al, 1998;Omtvedt et al, 2000), and AL proteins were found to be glycosylated more frequently than circulating non-amyloidogenic free LCs (Holm et al, 1986;Omtvedt et al, 1997). Despite this evidence, the precise role of this PTM has yet to be determined.…”
Section: Posttranslational Modifications and Oxidative Stressmentioning
confidence: 99%